The biblical imagination in the early works of Toni Morrison and Léonora Miano - (:unkn) unknown (My University, 2020)
Biblical text has been greatly influenced in the modern society by the novels that relayed it. Our focus will be on the interpretation and adaptation that’s been put in place toward biblical thematic and concept/images in connection with fictional novels. Therefore, we will try to grasp the aim of authors when it comes to transposing biblical text in literature. In order to fulfil our study, we have targeted three of Toni Morrison’s and Léonora Miano’s novels: The bluest eye, Sula and Song of Solomon for Toni Morrison; L’intérieur de la nuit, Les aubes écarlates and Contours du jour qui vient for the franco camerounian author. We can clearly see that both authors are converging towards the same goals or ideas in their desire explore the soul of their community and make theirs voice heard in the world. While trying to compare the work of both authors, our approach to analyse the Bible footprints within a specific collection of novels; and interpretations of the world’s vision of both authors will be examined from three angles: mythocritical, intertextual and narratological.
Keywords: African Research